2019
DOI: 10.1101/590398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of in vivo protein folding probability on local fitness landscapes

Abstract: It is incompletely understood how biophysical properties like protein stability impact molecular evolution and epistasis. Epistasis is defined as specific when a mutation exclusively influences the phenotypic effect of another mutation, often at physically interacting residues. By contrast, nonspecific epistasis results when a mutation is influenced by a large number of non-local mutations. As most mutations are pleiotropic, basal protein stability is thought to determine activity-enhancing mutational toleranc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The analogous behavior observed for these mutants in E. coli and correlation of misfolding effects with phylogenetic conservation is consistent with a selective pressure to avoid misfolding in vivo and with growing evidence that kinetic factors affect stable protein expression in cells (Fig. 3K) ( 20, 26, 60, 61 ). The strong dependence of activity on temperature and Zn 2+ concentration present during expression suggests that mutations promoting formation of the inactive state may disrupt co-translational folding ( 20, 62 ).…”
Section: Discussionsupporting
confidence: 81%
“…The analogous behavior observed for these mutants in E. coli and correlation of misfolding effects with phylogenetic conservation is consistent with a selective pressure to avoid misfolding in vivo and with growing evidence that kinetic factors affect stable protein expression in cells (Fig. 3K) ( 20, 26, 60, 61 ). The strong dependence of activity on temperature and Zn 2+ concentration present during expression suggests that mutations promoting formation of the inactive state may disrupt co-translational folding ( 20, 62 ).…”
Section: Discussionsupporting
confidence: 81%
“…At least two factors might hamper the success of sequence alignments for predicting substitution outcomes. First, most extant homologs differ at multiple positions, and non-additivity among some subsets of substitutions ("epistasis") can confound detection of signals associated with single amino acid changes (e.g., [34][35][36][37][38][39][40][41] ). Second, the rheostat/toggle/neutral character of a position could change during evolution (i.e., differ among homologs).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that epistasis is pervasive in real proteins, but its effect on evolution and the extent of higher-order interactions remains murky. Studies of single-site mutant libraries (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) and case studies of historical substitutions (43)(44)(45)(46)(47)(48)(49) have shown that mutations' effects often depend on the sequence background in which they occur. Studies that measure the effects of many pairs of mutations on a single function have shown that pairwise interactions reduce the accessibility of some two-step paths from a designated wildtype protein (50)(51)(52)(53).…”
Section: Introductionmentioning
confidence: 99%
“…Epistasis is clearly present in the genetic architecture of proteins (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), but its overall character and effects on evolutionary trajectories remain murky. Studies of pairs of mutations show that pairwise interactions can block some twostep paths around a designated wild-type protein (50)(51)(52)(53) and experiments on higher-order combinations have found that epistasis can reduce the number of functional intermediates that connect a designated pair of starting and ending proteins (54)(55)(56)(57)(58)(59)(60)(61)(62).…”
Section: Introductionmentioning
confidence: 99%